Income inequality and risk taking: the impact of social comparison information - Ulrich Schmidt; Levent Neyse; Milda Aleknonyte (Theory and Decision, 2019)
In contrast to the assumptions of standard economic theory, recent experimental evidence shows that the income of peers has a systematic impact on observed degrees of risk aversion. This paper reports the findings of two experiments examining the impact of income inequality on risk preferences and whether the knowledge of inequality mediates the decisions. In Experiment 1, participants who were recruited for a real-effort task were paid either a low wage or a high wage. Half of the participants were aware of the income inequality, while the other half were not. After completing their task, they were invited to invest a part of their salary in a risky asset. In Experiment 2, we replicated the same experiment in the laboratory with windfall endowments to test the consistency of results in the laboratory settings. The results of the first experiment show that high-wage subjects take higher risks than low-wage participants do if they are aware of the inequality in wages. This finding supports the idea that income comparisons shape risky decisions. In Experiment 2, on the other hand, we did not observe any significant differences in decisions. This may suggest that the income comparison is sensitive to house-money effect.
Keywords: 330; risk preferences; income inequality; relative income; social comparison